Preparing sandwiches, appetisers and salads - De Robbio, Michael; Inducil, Mark.; Sankey, Andrew; Video Education Australasia (Bendigo, Vic. : VEA, 2009)
"Having the skills and knowledge required to prepare and present appetisers, sandwiches and salads is crucial to successful operation of any commercial kitchen or catering business. This program takes you through the steps involved in making, preparing, and presenting these ever evolving dishes while discussing useful tips that will enhance the quality of your food preparation. Along the way we apply kitchen hygiene and safety, time management, how to minimise waste, and the historical development of the foods being prepared, while highlighting the best methods for storing both fresh and pre-prepared produce"-- Container.
Director, Mark Inducil ; producer, Michael De Robbio.
Presenter: Andrew Sankey.
Keywords: Appetizers; Cooking; Salads; Sandwiches